3x+c=cx-2

Subtract cx from both sides of the equation.

3x+c-cx=-2

Subtract c from both sides of the equation.

3x-cx=-2-c

Factor x out of 3x.

x⋅3-cx=-2-c

Factor x out of -cx.

x⋅3+x(-c)=-2-c

Factor x out of x⋅3+x(-c).

x(3-c)=-2-c

x(3-c)=-2-c

Divide each term in x(3-c)=-2-c by 3-c.

x(3-c)3-c=-23-c+-c3-c

Cancel the common factor of 3-c.

Cancel the common factor.

x(3-c)3-c=-23-c+-c3-c

Divide x by 1.

x=-23-c+-c3-c

x=-23-c+-c3-c

Simplify -23-c+-c3-c.

Simplify each term.

Move the negative in front of the fraction.

x=-23-c+-c3-c

Move the negative in front of the fraction.

x=-23-c-c3-c

x=-23-c-c3-c

Simplify terms.

Combine the numerators over the common denominator.

x=-2-c3-c

Rewrite -2 as -1(2).

x=-1(2)-c3-c

Factor -1 out of -c.

x=-1(2)-(c)3-c

Factor -1 out of -1(2)-(c).

x=-1(2+c)3-c

Move the negative in front of the fraction.

x=-2+c3-c

x=-2+c3-c

x=-2+c3-c

x=-2+c3-c

Solve for x 3x+c=cx-2